HOME CARE POST FEMUR FRACTURE SURGERY ON MR. A IN THE WATUBELAH AREA, CIREBON REGENCY IN 2024 - Leya Indah Permatasari; Aldi Ramadan; Dian Amelia; Hoirunnisa Hoirunnisa; Nanda Meilizha; Nurliana Nurliana; Seli Juliyanti; Uun Kunaena (Ann Publisher, 2024)
Home Care is a health service carried out at home and aims to improve, maintain, and increase the independence of patients and families. The home care activities at Mr. A aim to be a form of community service with the hope that the family can be independent in caring for Mr. A. The implementation of community service in the form of home care services uses a family nursing care approach, starting from conducting assessments, determining diagnoses, and providing interventions, documentation, and evaluations. The implementation of home care services is carried out for three days by providing education and wound care. After the wound was treated, Mr. A's wound no longer had fluid coming out of the wound, and when given education, Mr. A and his family understood what was conveyed.